2020
DOI: 10.3390/su12114394
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Relationships with Nature in Cities

Abstract: Limited exposure to direct nature experiences is a worrying sign of urbanization, particularly for children. Experiencing nature during childhood shapes aspects of a personal relationship with nature, crucial for sustainable decision-making processes in adulthood. Scholars often stress the need to ‘reconnect’ urban dwellers with nature; however, few elaborate on how this can be achieved. Here, we argue that nature reconnection requires urban ecosystems, with a capacity to enable environmental learning in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 121 publications
(161 reference statements)
1
16
0
Order By: Relevance
“…On the other hand, not only the school's curriculum has changed but today's pupils also grow up in a different socio-cultural environment as compared to those back in 2007. Screen time (media-based activities) that were not even available in the early years of the twenty-first century diminishes the time today's children spent in nature (Larson et al, 2019) and this might be one of the causes for a declining humannature-connection in general (Colding et al, 2020). Further investigation on the influence of pupils' screen time and time in nature on their species knowledge will be helpful for an explanation why there is such a decline over a decade.…”
Section: Decline Of Species Knowledge and Possible Reasonsmentioning
confidence: 99%
“…On the other hand, not only the school's curriculum has changed but today's pupils also grow up in a different socio-cultural environment as compared to those back in 2007. Screen time (media-based activities) that were not even available in the early years of the twenty-first century diminishes the time today's children spent in nature (Larson et al, 2019) and this might be one of the causes for a declining humannature-connection in general (Colding et al, 2020). Further investigation on the influence of pupils' screen time and time in nature on their species knowledge will be helpful for an explanation why there is such a decline over a decade.…”
Section: Decline Of Species Knowledge and Possible Reasonsmentioning
confidence: 99%
“…Alongside government directives for staying at home and social/physical distancing, health authorities including U.S. Centers for Disease Control and Prevention (CDC) and WHO emphasized the importance of regularly performing exercise to cope with the stress of quarantine, stay healthy, and maintain immunity [22]. Several studies argued that physical inability as a consequence of strict quarantine may be associated with increased risk of mental health outcomes as well as cardiovascular diseases, metabolic diseases, and cancer [23][24][25][26]. Thus, the COVID-19 pandemic along with other major environmental crises such as climate change shed a light on the need for better understanding of how to promote resilience or capacity of societies to deal with complex health crises [26].…”
Section: Introductionmentioning
confidence: 99%
“…However, to further overcome the human-nonhuman, mind-matter and subject-object dichotomies that obfuscate integrated forms of sustainability research and practice, there have been calls for more relational forms of sustainability research that integrate internal and external relationships with nature (Walsh et al 2021;West et al 2020). Indeed, the recent scholarship has emphasised the need for an embodied HNC approach that conceptualises HNC as an interplay between internal and external human and nonhuman nature including mind, body, environment and culture (Colding et al 2020;Cooke et al 2016;Raymond et al 2017). An embodied approach takes into account that "(…) humans are not just mentally, but also materially and physically immersed in their immediate environments" (Cooke et al 2016, p. 2).…”
Section: An Embodied Perspective On Human-nature Connectionmentioning
confidence: 99%
“…In this regard, Artmann et al (2020) applied the framework by Ives et al (2018) introducing the concept of Human-Food Connection (HFC) as an interpretation of HNC in the context of local food production and consumption. Urban food production and associated practices, such as urban gardening have been proposed as potential interventions to strengthen HNC in cities (Colding et al 2020;Cooke et al 2016;Turner 2011). As a focus of considerable research attention, many studies have suggested that by participating in community gardens or allotments, urban residents can profit from mental and physical well being, healthy food production, social cohesion and environmental learning (Breuste and Artmann 2015;Camps-Calvet 2016;Kingsley et al 2009).…”
Section: An Embodied Perspective On Human-nature Connectionmentioning
confidence: 99%